Playing Online Video Games as a Learning Strategy to Enhance EFL Learners’ Speaking Skill - Bennacer , Fouzia (Milev Journal of Research and Studies, 2022)
The present article discloses the results of a research that investigated the English Foreign Language (EFL) learners’ use of playing online digital videogames as a learning strategy to enhance their speaking skill. The study fits with the new teaching approach labelled edutainment. The research was quantitative distributing a questionnaire online to Algerian university learners belonging to different departments of English language and literature. Two hundered and ten learners whose level ranges from first year undergraduate to master two participated in the survey. The discussion of the results showed that learners do not play videogames for learning purposes, but they agreed with their positive impact on increasing vocabulary acquisition, enhancing pronunciation, lowering anxiety, and raising motivation which affects their speaking skill positively and unconsciously.